The Role of Local Character Values in Developing Social Studies Learning Materials to Improve Students National Insight - Agung Dwi Bahtiar El Rizaq; Sarmini Sarmini; Sunarto Sunarto (Universitas Negeri Surabaya, 2019)
Knowledge and cognitive development of individuals come from socio-cultural sources around themselves. This article aims to examine the use of local character values in the development of social studies teaching materials in schools. The method used is 4-D Thiagarajan model which has four stages; (1) Define, (2) Design, (3) Develop, and (4) Dessiminate. From the research process, there are significant differences between learning before using local character values and after using local characters. This is indicated by the difference in the value of the pre-test and post-test, after the treatment of the use of local character values in the IPS teaching and learning process the value of t_count shows greater than the t_table value of 1.7> 1.685 for 5%. The n-gain value of the pre-test and post-test was 0.58 in the medium category. This value shows the value of local character has a significant effectiveness in improving students national insight.